Critical temperatures and pressures, heat capacities, and thermal diffusivities of levulinic acid and four n-alkyl levulinates. (August 2019) - Nikitin, Eugene D.; Popov, Alexander P.; Bogatishcheva, Nataliya S.; Faizullin, Mars Z.
Highlights: Critical properties, heat capacities, thermal diffusivities of levulinic acid and n-alkyl levulinates were measured. Esters studied were from methyl to butyl levulinate. Data on heat capacity and thermal diffusivity cover the temperature range from 303.15 to 373.15 K at atmospheric pressure. Levulinic acid is a platform molecule in the process of conversion of biomass into fuels. Alkyl levulinates are used as oxygenate additives for diesel and gasoline fuels. Abstract: The critical temperatures, pressures, heat capacities, and thermal diffusivities of levulinic acid and methyl, ethyl, propyl, and butyl levulinates have been measured. Experimental critical constants of levulinic acid and alkyl levulinates have been compared with those calculated using the group contribution methods of Wilson/Jasperson, Lydersen, Constantinou/Gani, and Marrero/Gani. The temperature dependencies of heat capacities and thermal diffusivities have been approximated by a third-order and a first-order polynomial, respectively. The coefficients of these polynomials have been given. Experimental heat capacities have been compared with those estimated by the methods of Kolska et al. and Dvorkin et al. Using the experimental data, the thermal conductivities of alkyl levulinates have been calculated. These data have been compared to those calculated by the methods of Latini et al. and Sastri.